Feasibility of the breastfeeding peer support application—perspectives of peer supporters and breastfeeding mothers - Ikonen, Riikka; Niela-Vilen, Hannakaisa (Springer Science and Business Media LLC, 2026)
Background
Online breastfeeding peer support, which provides information, advice, emotional support, reassurance, and a sense of shared experience, is increasingly delivered through mobile applications as a relatively new form of digital peer support. This study examined the feasibility of a breastfeeding peer support application from the viewpoints of peer supporters and breastfeeding mothers.
Methods
A feasibility study with both qualitative and quantitative data, combining the perspectives of peer supporters and breastfeeding mothers, was conducted in Finland in 2022. The qualitative data were collected from breastfeeding peer supporters (n = 8) via focus groups and analyzed via content analysis. The quantitative data from breastfeeding mothers (n = 81) were collected via a structured survey embedded in the Breastfeeding Peer Support Application and analyzed with descriptive statistics.
Results
Four main categories describing the perspective of eight experienced peer supporters were created. First, controlling the burden of peer support was possible, as peer supporters were able to regulate their availability in the App. Second, peer supporters had a strong sense of duty, and some of the features of the App helped them avoid overusing their resources, but others did not. Thus, the peer supporters had to balance the sense of duty and the features of the App. Third, peer support contacts with breastfeeding mothers were mostly rewarding, but a few suddenly breaking and disappearing contacts caused frustration and insecurity. Both short and easy-to-solve contacts and long-term contacts were rewarding. The fourth main category illustrates that real-time support via the App is present and responds well to the increasing need for online support. On the basis of the survey completed by breastfeeding mothers (n = 81), they were satisfied with the App; it was ranked high in acceptability, appropriateness and usability regardless of mothers’ age, education or number of children.
Conclusions
The breastfeeding peer support application was shown to be a feasible tool from the perspectives of both trained peer supporters and breastfeeding mothers and was easily integrated into their daily lives. Most mothers found effective solutions to their breastfeeding challenges. Overall, the App was regarded as a highly promising tool for supporting breastfeeding.